Serum antibodies to surface proteins of Chlamydia trachomatis as candidate biomarkers of disease: results from the Baltimore Chlamydia Adolescent/Young Adult Reproductive Management (CHARM) cohort. (28th February 2022) - Marques, Patricia X; Wand, Handan; Nandy, Melissa; Tan, Chun; Shou, Huizhong; Terplan, Mishka; Mark, Katrina; Brotman, Rebecca M; Wilson, David P; Ravel, Jacques; Hsia, Ru-ching; Bavoil, Patrik M
Abstract: We previously observed that the nine-member family of autotransported polymorphic membrane proteins (Pmps) of Chlamydia trachomatis is variably expressed in cell culture. Additionally, C. trachomatis -infected patients display variable Pmp-specific serum antibody profiles indirectly suggesting expression of unique Pmp profiles is an adaptive response to host-specific stimuli during infection. Here, we propose that the host response to Pmps and other outer surface proteins may correlate with disease severity. This study tests this hypothesis using an ELISA that measures serum IgG antibodies specific for the nine C. trachomatis Pmp subtypes and four immunodominant antigens (MOMP, OmcB, Hsp60, ClpP) in 265 participants of the Chlamydia Adolescent/Young Adult Reproductive Management (CHARM) cohort. More C. trachomatis -infected females displayed high Pmp-specific antibody levels (cut-off Indexes) than males (35.9%–40.7% of females vs . 24.2%–30.0% of males), with statistical significance for PmpC, F and H ( P < 0.05). Differences in Pmp-specific antibody profiles were not observed between C. trachomatis -infected females with a clinical diagnosis of pelvic inflammatory disease (PID) and those without. However, a statistically significant association between high levels of OmcB-specific antibody and a PID diagnosis ( P < 0.05) was observed. Using antibody levels as an indirect measure of antigen expression, our results suggest that gender- and/or site-specific (cervix in females vs . urethra in males) stimuli may control pmp expression in infected patients. They also support the possible existence of immune biomarkers of chlamydial infection associated with disease and underline the need for high resolution screening in human serum. Abstract : The serum antibody response of Chlamydia trachomatis-infected patients against selected chlamydial surface proteins is associated with gender and disease severity.